Implementation impediments to institutionalising the practice of sustainable urban water management - Brown, R R (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
It is now well accepted that there are significant challenges to realising the widespread and self-sustaining implementation of sustainable urban water management. It is argued that these challenges are entrenched within the broader socio-political framework, yet often unsuccessfully addressed within the more narrow scope of improving technical knowledge and design capacity. This hypothesis is investigated through a comparative analysis of three independent research projects investigating different dimensions of the water cycle, including stormwater management in Australia and sanitary waste management and implementation of innovative technologies in the U.K. The analysis reveals significant and common socio-political impediments to improved practice. It was evident that the administrative regime, including implementing professionals and institutions, appears to be largely driven by an implicit expectation that there is a technical solution to solve water management issues. This is in contrast to addressing the issues through broader strategies such as political leadership, institutional reform and social change. It is recognised that this technocratic culture is inadvertently underpinned by the need to demonstrate implementation success within short-term political cycles that conflict with both urban renewal and ecological cycles. Addressing this dilemma demands dedicated socio-technical research programs to enable the much needed shift towards a more sustainable regime